Hubungan tingkat adiksi gadget dengan kejadian insomnia pada siswa SMPN 1 Palangka Raya - Kesuma, I Putu Gede Candra; Balyas, Abi Bakring; Toemon, Angeline Novia (Barigas: Jurnal Riset Mahasiswa, 2024)
Insomnia is one or more sleep disorders that include difficulty starting sleep, difficulty maintaining sleep so that often waking up from sleep, waking up too early in the morning and difficult to fall back asleep, poor quality sleep. Addiction is a condition in which a person is bound by his habits and will feel difficulty when he will be kept away or released from these activities, the negative impact of addiction gedged this study aims to determine the relationship between the level of addiction and the incidence of insomnia in students of SMPN 1 Palangka Raraya. This research was conducted at SMPN 1 Palangka Raya on October 23, 2023. This research method uses cross sectional, data collection using questionnaires and analytical data using spearman correlation, in this research obtained results from the chi square test and spearman correlation obtained P valule of 0.000  <0.05 and r value of 0.245.  In conclusion, there is a relationship with a low correlation strength between addiction and insomnia in SMPN 1 Palangka Raya students.